Biodiesel production from waste cooking oil: A review of prospects and challenges - Abdul Rasid, Ahmad Fuad; Muhammad Idris; Mohd Zamberi, Mahanum; Yang, Zhang (Penerbit Akademia Baru, 2024)
The consumption of fossil fuels is increasing as people become more reliant on them. It is consequently vital to discover more environmentally friendly and sustainable alternative energy sources. Because of its considerable potential to reduce greenhouse gas emissions and its renewable nature, biodiesel derived from WCO has gained attention as a feasible alternative. Enhancing product quality and guaranteeing consistent economic growth are substantial challenges. This investigation aims to assess the feasibility of utilizing WCO as a renewable resource to produce biodiesel. In particular, the investigation investigates the feasibility of obtaining cost-effective and high-quality biodiesel results. To optimize outcomes, this investigation implements a transesterification approach that employs calcium oxide catalysts. Biodiesel's economic value and environmental benefits are assessed through the Life Cycle Cost Assessment (LCCA) assessment method. WCO biodiesel exhibits a high conversion rate and favorable physicochemical properties, as indicated by the results. Therefore, WCO biodiesel can meet the worldwide demand for fuel. The results show that WCO biodiesel has favorable physicochemical properties and a high conversion rate. As a result, WCO biodiesel can meet global fuel demand. It has the potential to generate many benefits for the environment, but there are problems with the collection and processing of WCO. However, WCO collection and processing issues still exist. Biodiesel derived from WCO reduces harmful pollutants, improves public health and air purity, according to engine performance tests.